Linear approximation of a vectorial Boolean function using quantum computing. (30th December 2020) - Malviya, A. K.; Tiwari, N.
Abstract: A vectorial Boolean function takes multi-bit input and produces a multi-bit output. According to the input parameters, a vectorial Boolean function can be linear or non-linear. Non-linear vectorial Boolean functions have high importance in information theory and cryptology. Finding a linear approximation of a non-linear vectorial Boolean function is of high significance in these areas. Assuming that the quantum access to a vectorial Boolean function is provided, we present a quantum computing approach which can find the best linear approximation of the non-linear vectorial Boolean functions. The presented quantum approach is exponentially better than any known solution on the factors of querying the function, quantum circuit depth and memory requirements.